Oil palm empty fruit bunch biochar: characterization and potential usage as soil amendment for its nutrient retention capacity in soil - Tan, Wei Loon; Abu Bakar, Rosenani; Ahmad, Siti Hajar; Ishak, Che Fauziah (2012)
Biochar soil amendment is beneficial not only to sequester carbon for climate change mitigation but also to improve soil health and crop performance. A potential feedstock that can be used as a biochar is oil palm empty fruit bunch, a waste produced in the palm oil industry which is abundant and posed an environmental threat if not properly managed. However, different types of biochar exhibit variation in characteristics and properties. Therefore, this study was conducted to determine the characteristics of EFB biochar and its potential use as soil amendment. EFB biochar was collected and characterized (pH, total C, total N, nutrient content, cation exchange capacity and surface morphology). A field container experiment was also conducted to study the effect of EFB biochar soil amendment on soil nutrient leaching. The characterization study indicated that EFB biochar to exhibit beneficial characteristics. In the field container experiment, treatments with EFB biochar amendment showed significant lower nutrient leached compared to the control.